2012
DOI: 10.1111/j.1365-2982.2011.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Weak and absent peristalsis

Abstract: Background Weak and absent esophageal peristalsis are frequently encountered esophageal motility disorders, which may be associated with dysphagia and which may contribute to gastroesophageal reflux disease. Recently, rapid developments in the diagnostic armamentarium have taken place, in particular, in high-resolution manometry with or without concurrent intraluminal impedance monitoring. Purpose This article aims to review the current insights in the terminology, pathology, pathophysiology, clinical manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 61 publications
2
52
1
6
Order By: Relevance
“…Thus the relation between pre-operative IEM and surgery outcome should be interpreted with caution. 15 Many patients with pre-operative minor disorders of peristalsis (impaired clearance) may actually benefit from Nissen fundoplication since the esophageal motility improves post-operatively, as it was demonstrated in this study. We believe that tailoring the operation to the degree of IEM is often not required to achieve a successful symptomatic and functional post-operative outcome.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Thus the relation between pre-operative IEM and surgery outcome should be interpreted with caution. 15 Many patients with pre-operative minor disorders of peristalsis (impaired clearance) may actually benefit from Nissen fundoplication since the esophageal motility improves post-operatively, as it was demonstrated in this study. We believe that tailoring the operation to the degree of IEM is often not required to achieve a successful symptomatic and functional post-operative outcome.…”
Section: Discussionsupporting
confidence: 61%
“…IEM was previously reported by other researchers as the most prevalent esophageal motor disorder in GERD, found in 21-38% of patients in a large series, and its presence was associated with the severity of acid exposure and reflux symptoms. 15 Minor motility disorders that meet the criteria for IEM are probably the least studied manifestations of esophageal dysfunctions due to apparent lack of therapeutic options. There is no pharmacological treatment that reliably restores smooth muscle contractility and esophageal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Another study revealed that the main presenting symptom was dysphagia in 65 patients with nonspecific esophageal motility disorders, 6 which may likely be associated with degeneration and atrophic changes in the layers of the esophageal smooth muscle. 16 One interesting study from Japan investigated the esophageal motility in patients with globus sensation who were refractory to PPI treatment. Out of the total of 119 patients who were refractory to PPI treatment, 47.9% had abnormal esophageal motility, of which 66.4% had IEM.…”
Section: Discussionmentioning
confidence: 99%